Resistência antimicrobiana na avicultura: Efeitos do uso profilático de ceftiofur e do tratamento químico da cama na disseminação de betalactamases - Saraiva, Mauro de Mesquita Souza (2018)
The antimicrobial use in poultry farming is a common practice around the world, aiming to increase animal productivity. However, the growing emergence of resistant bacterial species to these drugs has concerned poultry producers and consumers. Gram-positive bacteria as Enterococcus spp. and Staphylococcus aureus, and Gram-negative bacteria as Escherichia coli, Campylobacter spp. and Salmonella spp., are among the main species commonly isolated from broilers and layers, with highest antimicrobial resistance. These species are often described as resistant to different antimicrobial classes include these considered of critical importance to animal and human health, as cephalosporins. The resistance mechanisms to these drugs are quite diverse, and the main of them is the enzymatic mechanism, such as extended-spectrum β-lactamases encoded by genes present in chromosomes and mobile elements. The blaTEM-1, blaPSE and blaCTX-M-1 genes are the most reported in isolated bactérias from the poultry industry. Two experiments were carried out at the Animal Origin Products Analysis Laboratory (LAPOA/CCA/UFPB). Chapter II presents data from the first experiment to evaluate the off-label use of ceftiofur in one-day-old chicks, mimicking common prophylactic use in poultry farms together with the Marek’s vaccine, and the occurrence of β-lactamase-producing Escherichia coli. We used 168 chicks arranged into ceftiofur treated and untreated groups. The ceftiofur application in chicks positively influenced the ESBL occurrence in the recovered E. coli isolates (86%; p <0.001). All ESBL-producing E. coli presented the blaCTX-M and blaSHV genes. No isolates were positive for plasmid-mediated AmpC genes tested in this study. The Bayesian approach showed greater probabilities of ESBL-producing E. coli occurrences in the ceftiofur-treated groups, as well as days 7 and 14, compared to the untreated group and the other experimental days, respectively. In Chapter III data are presented referring to the second experiment that aimed to evaluate the effects of chemical residues on different materials 17 used as poultry litter on the conjugation rate of ESBL-plasmids in E. coli. It was used a 2x5 design, with two different litter materials (cane bagasse and wood shavings) and five treatments (control, quicklime, aluminum sulphate, copper sulphate and superphosphate). Groups with no chemical additions demonstrated higher conjugation rates. In the cane bagasse litter showed beneficial interaction with the use of superphosphate (p <0.001). When the wood shavings were used as a substrate, the lowest rates were obtained with the use of quicklime and copper sulphate. Lower conjugation rates of ESBL-plasmids were obtained in cane bagasse. The ceftiofur use in one-day-old chicks together with the Marek vaccine raises the resistant E. coli occurrence in short-term. The chemical presence can affect the conjugation of ESBL-plasmids between E. coli, despite the influence of environmental factors on the horizontal transfer of mobile elements.